PEMANFAATAN WORDWALL DALAM MENINGKATKAN MINAT BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 29 MUARO - Ermawasari; Desyandri (STKIP Subang, 2024)
Mathematics subjects are often considered boring or uninteresting. Because there are quite complex materials in it. Such as the problems that occur in fourth grade students at SDN 29 Muaro, Sijunjung District who experience learning difficulties in Mathematics learning. Therefore, researchers conducted research to solve these problems. The study of this article aims to describe and explain how to utilize the wordwall application to develop students' interest in Mathematics learning for fourth grade students at SDN 29 Muaro, Sijunjung District. In this study, the method used was a qualitative method. Fourth grade students as research subjects, while teachers as informants who then collaborated with researchers. The results of the study stated that fourth grade students at SDN 29 Muaro, Sijunjung District experienced problems in Mathematics learning, namely students lacked concentration, and also lacked interest in learning. The solution used by researchers to overcome this was to conduct experiments by utilizing the wordwall application in evaluation activities at the end of learning. Researchers collaborated with grade IV teachers of SDN 29 Muaro, Sijunjung District in utilizing a learning media, namely a wordwall application integrated with the PBL (problem based learning) learning model. The use of the wordwall application has been proven to increase students' learning motivation. Seen from students' attitudes during learning and student learning outcomes after learning Mathematics in the Merdeka Curriculum